Joining alumina to titanium alloys using Ag-Cu sputter-coated Ti brazing filler - Emadinia, Omid (2020)
The joining of alumina (Al2O3) to γ-TiAl and Ti6Al4V alloys, using Ag-Cu sputter-coated Ti brazing filler foil, was investigated. Brazing experiments were performed at 980 °C for 30 min in vacuum. The microstructure and chemical composition of the brazed interfaces were analyzed by scanning electron microscopy and by energy dispersive X-ray spectroscopy, respectively. A microstructural characterization of joints revealed that sound multilayered interfaces were produced using this novel brazing filler. Both interfaces are composed mainly of α-Ti, along with Ti2(Ag,Cu) and TiAg intermetallics. In the case of the brazing of γ-TiAl alloys, α2-Ti3Al and γ-TiAl intermetallics are also detected at the interface. Bonding to Al2O3 is promoted by the formation of a quite hard Ti-rich layer, which may reach a hardness up to 1872 HV 0.01 and is possibly composed of a mixture of α-Ti and Ti oxides. Hardness distribution maps indicate that no segregation of either soft or brittle phases occurs at the central regions of the interfaces or near the base Ti alloys. In addition, a smooth hardness transition was established between the interface of Al2O3 to either γ-TiAl or Ti6Al4V alloys.